Self-Monitoring Experiences of Children with Type 1 Diabetes in Managing the Disease - Gramauskaitė, Gabrielė; Mažionienė, Asta; Gedrimė, Lina (Slauga. Mokslas ir praktika, 2022)
Diabetes mellitus (CD) is one of the most common endocrine diseases and one of the most common chronic diseases in the age group of children. The results of global studies show a threatening increase in the incidence of type 1 diabetes, not only in adults but also in children. Diabetes has a major impact on a patient’s daily life. Regular glucose testing, injections, nutrition, and exercise control constantly remind you of the disease and disrupt normal life. This especially affects children with diabetes and their families. The diabetes management routine is not easy for either the child or his or her parents. Overcoming psychological and social difficulties is often difficult, especially if strict and intensive diabetes control is required. The burden of the disease is felt in all areas of the child’slife - at home, kindergarten, school. On the one hand, improved diabetes control guarantees a long erlifeexpectancy for patients. Failure to behave properly in the face of a problematic or conflict situation can develop into self-control behavior. Such behavior in diabetes leads to frequent hospitalizations, more frequenta cute complications, and early development of late complications.